A comparative account of the bilingual education programs in Malaysia and the United States - Parilah Mohd Shah,; Fauziah Ahmad, (Penerbitan UKM, 2007)
This paper looks at major challenges encountered in the stipulation and implementation of bilingual education in Malaysia and the United States. It analyses in a comparative manner the language history and profile; the rationale and types of bilingual programs; the challenges faced in the development and implementation of bilingual programs in the aspects of linguistic perception and resources; and the general solutions to overcome the problems. With respect to the linguistic situation, English has a strong influence on the society in the two countries, with English holding a much higher position in the United States. Bilingual education in Malaysia is geared more towards the maintenance of the mother tongue than the one in the United States. The United States’ bilingual program is more transitional in nature, although there are some schools that conduct maintenance programs. Some of the problems faced by the two countries are linguistic perception, shortage of teachers, lack of materials and the allocation of funds. Both countries embark on the same solutions to the problems. To improve the linguistic perception, the media plays a significant role by holding a system-wide public relation campaign to reduce linguistic competition. Availability of resources is made easily accessible by the two countries so that there is an increase in number and amount. These two countries accept constructive criticisms on their existing bilingual education programs; evaluation of this nature could ensure the best bilingual education for all